The Existence Of Memacak Tradition As A Da’wah Medium In Lombok (Structural-Functionalism Perspective) - Kurniawan, Andri (KOMUNIKA, 2024)
Social change and the development of the times present challenges to cultural traditions (local wisdom) today. The declining interest of younger generations due to digital media exposure has gradually led to local wisdom being relatively abandoned. However, the cultural community's need for religious connection cannot be denied. The Memacak tradition as a medium of da'wah holds a special place in community life. This research employs a qualitative approach with a phenomenological perspective through observation and documentation techniques. The findings reveal that the existence of the Memacak Tradition can be observed through the activities and roles attached to it. These functions include entertainment media, da'wah media, and warning (muhasabah), which are inseparable from the involvement of several elements: community and religious leaders as social control, the Sabuk Belo customary institution as a forum for potential empowerment, regeneration, and cultural preservation by involving the community in various cultural events.